FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KETIDAKPATUHAN PENDERITA TUBERKULOSIS DALAM BEROBAT DI POLIKLINIK DOTS RSUP SANGLAH DENPASAR - Bagiada, I Made; Putri Primasari, Ni Luh (journal of internal medicine; Vol. 11, No. 3 September 2010)
Tuberculosis (TB) is a major public health problem in the world, especially in developing countries such as Indonesia. It remains a major contributor to the global burden of disease and has received considerable attention in recent years, particularly in developing countries. In our country, there is a little information about factors that can predict the adherence of TB patients. The objective of this study was to know factors contributing in non-adherence TB patients in polyclinic DOTS RSUP Sanglah Denpasar. This study was a cross-sectional descriptive study of 15 adult newly diagnosed TB patients. Patients interviewed with questionnaires consist of demographic and reasons of their non-adherence for TB treatment. About 12 (80%) of TB patients were male. We didn?t ! nd much different in knowledge, work, educational status, and home distance among TB patients to in" uence the adherence of the patients. The most important factor in" uencing the adherence of TB patients were drug side effects. The drug side effects were gastritis and skin itch (found in 10 and 3 patient respectively). Another reason for non-adherence in TB treatment were over estimated and cost. Adherence was one of the potential factors to increase cure rate in TB patients. Non- adherence not only decreasing cure rate in TB patients, but also as a risk for MDR TB. By determining inhibition factors in the treatment of TB patients, we can improve the effectiveness of TB treatment.
Keywords: adherence, tuberculosis, DOTS PENDAHULUAN